Quaternary Landforms and Basin Morphology Control the Natural Eutrophy of Boreal Lakes and Their Sensitivity to Anthropogenic Forcing - Tammelin, Mira; Kauppila, Tommi (Frontiers in Ecology and Evolution, 2018)
Both natural and anthropogenic changes in boreal lakes have been studied utilizing paleolimnological methods, but the spatial variation in the natural conditions of lakes and its connection to geological factors has drawn less attention. Our aims were to examine the spatial distribution of naturally eutrophic lakes on the previously glaciated terrain of central-eastern Finland and the relationship between pre-human disturbance water quality and geological factors related to the basins and their catchments. Furthermore, we studied the pre- to post-human disturbance changes in the diatom assemblages and water quality of 48 lakes (51 sampling sites) across the pre-disturbance phosphorus gradient by using the top-bottom sampling approach and multivariate statistics. According to our results, naturally eutrophic boreal lakes are more common than previously thought, occurring on fine-grained and organic Quaternary landforms, including fine-grained till. Our study emphasizes the importance of the previously overlooked matter of till grain-size variation as a driver behind the spatial variation in the natural trophic states of boreal lakes. The location of a lake in the hydrologic landscape and basin morphology appear to be important factors as well. Shallow, naturally eutrophic lakes with short water residence times and high catchment area to lake area and volume ratios have been particularly sensitive to anthropogenic forcing. Our results indicate that cultural eutrophication is not the only water protection challenge for the relatively remote and dilute boreal lakes, but salinization and alkalinization are also serious threats that should be taken into account. Therefore, it is crucial to consider the notable variation in the natural conditions of boreal lakes in addition to mitigating the effects of anthropogenic forcing, such as nutrient loading, catchment erosion, salt pollution, and climate change, in order to achieve efficient water protection.